Agenda for Hope: Preserving and Transforming Philippine Identity and Culture - Sicam, Paulynn Paredes (Archīum Ateneo, 2009)
In the heightened competition that characterizes globalization, knowing one's culture and keeping in touch with its most intimate values and aspirations can give the individual plenty of needed comfort. Without a sense of inner security that our culture, values, and aspirations provide, it is easy to succumb in the heat of battle. - From the Introduction by Fernando N. Zialcita.